Therapeutic programs and outcomes for pesons suffering from posttraumatic stress disorder in the balkans - Frančišković, Tanja (2005)
The treatment programs options for war traumatised persons were described and the programs organised in Rijeka psychotrauma center.Some evaluation result were presented and discused.